The Role of Tourism Awareness Groups in increasing Tourist Visits in West Bandung Regency (Case Study at Ciburuy Tourism Object) - Kristian, Indra (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This study aims to analyze the performance of the Ciburuy Village Tourism Awareness Group. The results of this research are expected to be an impetus for the Ciburuy Village Tourism Awareness Group to further improve the performance of their organization. This type of research uses a qualitative descriptive research type. Data collection consisted of interviews with informants and informants, both oral and structured interviews, such as observations at research locations, and documents available at research-related institutions. Data analysis techniques in qualitative research. The results of this study indicate that the performance of the Ciburuy Village Tourism Awareness Group is fairly good and the objectives of the Tourism Awareness Group. This can be seen from the 4 indicators of performance evaluation, namely (1) Efficiency, (2) Effectiveness, (3) Fairness, and (4) Responsiveness. As an indicator of effectiveness, the Ciburuy Village Tourism Awareness Group still has to improve the quality of the human resources of its members, which is the main organizational factor.